Uma sistematizaç\~ao da discuss\~ao sobre heterogeneidade industrial: Um olhar para além das regi\~oes brasileiras. O caso do Centro-Oeste brasileiro - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The purpose of this research was to show to what extent the problem of industrial heterogeneity is rooted in multi-scalar regional economic structures, particularly in the Brazilian Midwest from 2000 to 2010. Therefore, the technical features of the literature were used and adopted the analytical descriptive and statistical method. The results show that, at the regional level, for the years 2000 and 2010, there is a strong heterogeneity between the North, Northeast, South and Southeast. This same pattern is also found for the Federation Units (FUs) and the micro-regions and municipalities in the Midwest. Finally, the analysis of labor productivity growth rate notes that those municipalities that showed labor productivity index values higher than state averages are in specific portions of the territories of the states of Goiás, Mato Grosso and Mato Grosso southern.
Keywords: R11; 330; industrial heterogeneity; labor productivity; Midwest